Effect of Ag Nanoparticle on PLA/PEG Blend: A Study of Physical, Thermal Characterization, Shape Memory Assessment and Antimicrobial Properties - Kok, Mediha; Pekdemir, Mustafa Ersin; Tatar, Cengiz; Karagulle, Burcu; Pekdemir, Sibel Selcuk; Tatar, Beyhan; Oner, Ecem Ozen (Springer Int Publ Ag, 2024)
Composite films with Ag nanoparticles, which are active in biological applications such as biosensors, wound healing and cancer treatment, have been obtained in recent years on a blend consisting of polylactic acid and polyethylene glycol, which has the feature of working shape recovery. The characteristic signals of PLA and PEG were determined by making functional group analyses with attenuated total reflection infrared spectroscopy (ATR-IR) of polymer composite films obtained by the solution casting method. From the results of thermal analysis with thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC), it can be interpreted that Ag nanoparticle increases the initial decomposition temperature (Ti) of the polymer blend, that is, increases its thermal stability. The use of a high PEG ratio showed that the droplets in the scanning electron microscopy (SEM) images of the blend were large, while it was observed that these droplets were almost filled with the increasing Ag nanoparticle ratio. The characteristic XRD diffraction angles of Ag nanoparticles were determined more clearly in the composite containing 20% Ag at 2 theta = 38.1 degrees, 44.5 degrees, 64.6 degrees and 77.3 degrees. Finally, when the antimicrobial activities of the composites on L. Monocytogenes, C. perfringens, P. aeruginosa and E. coli O: 157 bacteria are examined, the antimicrobial activity with the highest Ag percentage proves the antimicrobial property of Ag.
Keywords: Silver nanoparticle; Bioplastics; PLA; Antimicrobial; Composite